Challenges in the Field of Sediment Monitoring in Ukraine in the Context of European Integration Requirements (Using the Danube Basin as an Example) - Nasiedkin, Ye. I.; Havryliuk, R. B. (Ukrainian Geographical Journal, 2025)
The publication addresses the issue of the state and development of river sediment monitoring, particularly as part of the European Union Water Framework Directive (EU WFD) implementation standards. A general terminological basis for their types, as specified in the relevant EU guidance documents, as well as requirements for controlling their qualitative and quantitative indicators, has been established. The state and development of the relevant observation system in Ukraine is considered using the example of the Danube basin, and ways of creating the necessary conditions for its improvement and harmonization with relevant European networks are discussed. The main threats to the harmonious development and sustainable functioning of transboundary river basins are outlined, associated with the redistribution of sediment runoff volumes in their individual sections and the emission of pollutants in their composition. The feasibility of conducting complex field observations of the mobile component of sedimentary matter to understand the relevant natural and anthropogenic processes, thereby informing scientifically based management decisions to improve the ecological state of water bodies, is substantiated. The study is based on both data obtained during the analysis of the regulatory framework of the EU and Ukraine within the framework of the harmonization and implementation of the WFD requirements and on the results of the most significant projects of the EU Danube countries on sediment management within the Danube basin, which have been implemented over the last decade. Information obtained during the implementation of the initiated continuous monitoring of suspended solids in the lower Danube, as part of the project’s tasks, “Innovative sediment management structure (SUstainNable DANube black Sea system (SUNDANSE)),” was also included.